2009
DOI: 10.1158/0008-5472.can-08-2690
|View full text |Cite
|
Sign up to set email alerts
|

Spleen Tyrosine Kinase Functions as a Tumor Suppressor in Melanoma Cells by Inducing Senescence-like Growth Arrest

Abstract: Loss of tumor-suppressive pathways that control cellular senescence is a crucial step in malignant transformation. Spleen tyrosine kinase (Syk) is a cytoplasmic tyrosine kinase that has been recently implicated in tumor suppression of melanoma, a deadly skin cancer derived from pigmentproducing melanocytes. However, the mechanism by which Syk suppresses melanoma growth remains unclear. Here, we report that reexpression of Syk in melanoma cells induces a p53-dependent expression of the cyclin-dependent kinase (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
67
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 43 publications
(59 reference statements)
3
67
1
Order By: Relevance
“…In this study, kinase-deficient Syk inhibited the tumor-suppressive potential of wildtype Syk indicating that its kinase activity was essential in mediating the antitumor effect. Recently, it has been found that Syk functions as a tumor suppressor in melanoma cells by inducing the p53-dependent expression of p21 cip1 (26). Our data suggest a similar mechanism may be operative in CLL cells.…”
Section: Discussionsupporting
confidence: 64%
“…In this study, kinase-deficient Syk inhibited the tumor-suppressive potential of wildtype Syk indicating that its kinase activity was essential in mediating the antitumor effect. Recently, it has been found that Syk functions as a tumor suppressor in melanoma cells by inducing the p53-dependent expression of p21 cip1 (26). Our data suggest a similar mechanism may be operative in CLL cells.…”
Section: Discussionsupporting
confidence: 64%
“…14 SYK has been shown to downregulate the transcription of cell-cycle progressive genes, such as CCND1, CCNA1, AKT1, and FOSL1. 5,6,26 On the other hand, the re-expression of SYK has been demonstrated to induce a TP53-dependent accumulation of CDKN1A and a senescence-like growth arrest in melanoma cells. 6 However, we did not find significant differences in mRNA levels of CCND1 and CDKN1A in Huh7 cells with and without SYK induction (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, SYK expression has been demonstrated in numerous nonhematopoietic cells, and its downregulation has been shown to be involved in tumor formation and progression. [3][4][5][6] The transfection of SYK into an SYK-negative cancer cell line dramatically inhibited its cell growth, migration, and invasion. [3][4][5][6] Conversely, the knockdown of SYK in SYK-positive breast cancer cells increased proliferation and invasion.…”
mentioning
confidence: 99%
See 2 more Smart Citations